STUDI KOMPARATIF USAHATANI PADI SEMI ORGANIK DAN KONVENSIONAL DI DESA WATUKEBO KECAMATAN BLIMBINGSARI KABUPATEN BANYUWANGI - Ani Domiah; Jani Januar (University of Jember, 2018)
The rising of semi-organic rice farming in Watukebo Village is due to the doubthness in implementing the semi-organic system. Semi-organic rice farm system require considerable cost savings compared to conventional rice and in the short-term, semi-organic rice production will generally decline. The study was conducted in the Watukebo Village Banyuwangi Regency intentionally. The sample are taken by using total sampling method for semi-organic rice farmers and quota sampling technique for conventional rice farmers. The data used are primary data and secondary data. The Tools of analysis data used are income analysis, R/C ratio analysis, and Cobb-Douglas production function analysis. The results showed that : (1) there was no significant difference between the average income of semi-organic rice farmers and conventional rice farmers, (2) there was no significant difference between the average of cost efficiency of semi-organic rice farming with conventional rice farmers in Watukebo of Blimbingsari, and (3) factors that influence the production of semi organic rice significantly are land area, organic fertilizer, and urea fertilizer. Factors affecting the conventional rice production significantly are the number of seeds and labors.